Preparation of chemically modified sago bark for oil sorption - Muhamad Farid, bin Mohammed Noh (Universiti Malaysia Sarawak (UNIMAS), 2014)
Sago (Metroxylon spp.) bark is a waste material in the sago production industries. The bark of sago has potential application as a low cost and effective oil sorbent. Raw sago bark (SB) was esterified using stearic acid to afford modified sago bark (MSB) with greater hydrophobicity compared to untreated SB. The esterification of SB was conducted by the addition of stearic acid to the SB with ratio (2:1), in the presence of difference percentage of catalyst (5, 10, 15 and 20%) under refluxing ethyl acetate.